Enhanced thermoelectric properties of n-type Ti-doped PbTe. (2019) - Loutati, Ariel; Zuarets, Shir; Fuks, David; Gelbstein, Yaniv
Abstract: Thermoelectric (TE) generators, converting waste heat to electricity regain their attractiveness for reduction of fossil fuels' reliance, and consequently minimizing adverse environmental effects. Such generators are based on an electrical series connection of TE couples, which consist n- and p- type semiconducting legs divided by metallic bridges. While for intermediate temperatures of up to 500 ° C, n-type PbTe was extensively studied and employed in commercial TE power generation applications, its maximal efficiency, as was reflected by the TE figure of merit, ZT, was in most of the cases maximized at a narrow temperature range for any given donor dopant concentration. The most commonly applied donor dopants are iodine and bismuth. Yet, some interesting characteristics were recently proposed upon using Ti as a donor dopant. Up to date an impressive maximal ZT of ∼1.2 was obtained at 500 ° C, upon doping of PbTe by 0.1 at.% Ti, while no lower concentrations were ever investigated. In the current research a lower, 0.05 at.% Ti doping level was applied, leading to the highest ever reported ZT values, for any given Ti doped PbTe, up to 350 ° C. Since the chemical compatibility of Ti with PbTe, as a metallic bridge in such couples, is well established, mainly due to its low diffusion rates, the potential of generating a stable Ti-doped functionally graded n-type PbTe material, with enhanced TE performance, is currently being proposed.